2020
DOI: 10.5005/jp-journals-10005-1817
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Knowledge and Attitude of Expectant Mothers Regarding Effect of Their Oral Health and Its Influence on the Infant Oral Health

Abstract: A bstract Introduction Good oral health during pregnancy and infancy is important for the overall health and well-being of mother and child, respectively. Aim To assess the knowledge and attitude of expectant mothers regarding the effect of their oral health and its influence on infant oral health. Materials and methods A cross-sectional study was conducted among expectant mothers. They were randomly selected from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…This could be explained by the fact that mothers with a higher educational level may have better discernment to choose the appropriate sources of information to adopt healthy practices. Likewise, women with a higher educational level may have better oral health literacy and a greater ability to choose a health service that is appropriate to their needs [40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…This could be explained by the fact that mothers with a higher educational level may have better discernment to choose the appropriate sources of information to adopt healthy practices. Likewise, women with a higher educational level may have better oral health literacy and a greater ability to choose a health service that is appropriate to their needs [40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a recent meta-analysis by Riggs et al (2019) [120] found moderate evidence that educational programs may be more effective than other types of interventions in preventing early childhood caries. However, studies from different populations [121] , [122] , [123] , [124] agreed that the knowledge and attitudes of mothers regarding the association of their oral health with the oral health of the child was still insufficient. For instance, a study performed with an Italian population reported that about 53.6% of the 304 parents were not aware of the potential vertical transmission of cariogenic bacteria through saliva, with 53% of parents reporting to taste the food of the infant and 38.5% admitting to share cutlery with the infant [123] .…”
Section: Clinical Relevance Of the Influence Of The Mother In Early L...mentioning
confidence: 99%
“…Compared to a traditional technique, the interview motivational suggests an intervention where learning is focused on identifying and remove barriers that prevent behavior modification and encourage the participant to reflect on changes that could be made from their own perspective to improve self-efficacy. When self-efficacy is improved, the chances of behavioral changes increase [11], [12].…”
Section: Introductionmentioning
confidence: 99%